Ukuran Perusahaan Memoderasi Profitabilitas, Leverage dan Intensitas Modal Terhadap Penghindaran Pajak - Vi Sonia; Barlia Annis Syahzuni (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to identify and analyze the effect of profitability, leverage, and capital intensity on tax avoidance, with firm size as a moderating variable. The research focuses on industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study population consists of 67 companies within the industrial sector throughout the observation period. Based on specific criteria, such as firms consistently operating in the industrial sector from 2022 to 2024, a final sample of 30 companies was obtained. With a four-year observation period, this research generated a total of 90 panel data observations. The study employs a quantitative approach using Moderated Regression Analysis (MRA) to test the moderating role of firm size in the relationship between independent variables and tax avoidance. The results indicate that profitability, leverage and capital intensity also show negative effects. Furthermore, firm size does not strengthen the relationship between profitability, leverage, and capital intensity with tax avoidance. The role of agency theory provides an explanation for firm size as a moderating variable. Larger firms are subject to greater public exposure and stricter monitoring, which is expected to reduce tax avoidance practices. The research findings indicate that the tendency to engage in tax avoidance practices is more closely associated with the level of profitability than with the size of the company.